THE DEVELOPMENT OF MAGAZINE BOOK TO IMPROVE STUDENT’S READING SKILL OF AGRIBUSINESS AND AGRICULTURAL PRODUCT PROCESSING PROGRAM AT SMK NEGERI 2 RANTAU UTARA - Adli Madilfa; Harahap, Anna Leli; Marpaung, Muhammad Fauzi Romadhon (Journal of English Education and Linguistics, 2025)
This study aims to design supplementary instructional materials in the form of a recipe-themed magazine tailored for vocational students in the Agribusiness and Agricultural Product Processing program. Conducted between February and March, the research applies the ADDIE development framework-comprising Analysis, Design, Development, Implementation, and Evaluation phases. The participants included 20 Grade XI students. Data collection tools included validation forms, pre- and post-tests, interview protocols, and observation checklists. The material was deemed appropriate for educational use based on expert validation scores exceeding 62%, and its impact on reading skill improvement was measured through pre- and post-assessments. The findings confirmed the effectiveness of the developed material, with validation results from media experts (88.28% and 85%) and language experts (86%) indicating high feasibility. Students’ reading scores improved from a pre-test average of 65.9 to a post-test average of 71.3, affirming the magazine’s potential to serve as an effective learning support.